Impedance spike cut-off enhances safety of CLOSE-protocol guided ablation of atrial fibrillation. (19th May 2022) - Krahnefeld, O; Agdirlioglu, T; Poley, P; Weil, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Catheter ablation (CA) with radiofrequency (RF) energy using the CLOSE protocol has proven safety and efficacy in a large prospective multicenter study (1) with a rate of pericardial tamponade (PT) as low as 0.9%, thus with lower PT risk than reported by previous register data for PVI (2). PT may still become hazardous in the era of uninterrupted anticoagulation and may require urgent surgical repair. Steam pop is the major cause of PT during PVI with RF ablation and is usually preceded by steep impedance rise measured between tissue and tip of the RF catheter. The STOCKERT SMARTABLATE RF Generator as a core part of technology for CLOSE protocol guided PVI offers the opportunity to automatically stop RF energy delivery within 0.5 seconds if catheter impedance rises above a predefined value: impedance spike cut off (ISCO). The standard – manufacturer recommended – value for ISCO is 50 Ohms per 0.5 seconds. Purpose: To investigate the effect of reduced ISCO during CLOSE protocol guided catheter ablation of AF on the occurrence of acute PT and pericardial effusion (PE) in a large single center series. Methods: We performed CLOSE protocol guided PVI procedures using Biosense Webster CARTO PRIME 3D navigation system, Smarttouch SF ablation catheter, VIZIGO steerable sheath, invasive blood pressure measurement via radial artery. We changed the STOCKERT SMARTABLATE generator settings to ISCO of 25 Ohms per 0.5 seconds. Cut off during ablation by ISCO led the operator to reduce contact force, angulation/orientation of catheter/steerable sheath, changing to jet ventilation if mechanical ventilation was present. A retrospective analysis of all procedures was performed. Investigation for PT by echocardiography was performed for every drop < 90mmHg systolic blood pressure, immediately after and one day post ablation. Statistical analysis was performed on the evaluable population. Results: During 31 months of observation we performed 627 CLOSE protocol guided procedures: 409 PVI only, 218 PVI with additional ablations (cavotricuspid isthmus, slow pathway, additional LA lines, ethanol ablation of vein of marshall). We observed 3 (0.5%) PT immediately at the end of the procedure and no additional relevant PE the day after CA. Of the 3 PT, one patient needed urgent surgical repair and two were managed conservatively with pericardiocentesis and retransfusion. Conclusions: CLOSE protocol guided PVI is a very effective and safe intervention for treatment of AF. In the multicentre VISITAX trial, the rate of PT was reported with 3 events per 329 patients (0.9%). By reducing ISCO to 25 Ohms per 0.5 seconds, we could half the rate of PT found in the VISITAX trial. The generator cut off at ISCO of 25 Ohms per 0.5 seconds indicates a potentially dangerous position for ablation. Our data are limited due to the retrospective monocentric design and therefore the aformentioned approach should be evaluated prospectively.